In vitro pre-vascularization strategies for tissue engineered constructs – bioprinting and others - Liew, Andy Wen Loong (2018)
Tissue-engineered products commercially available today have been limited to thin avascular tissue such as skin and cartilage. The fabrication of thicker, more complex tissue still eludes scientists today. One reason for this is the lack of effective techniques to incorporate functional vascular networks within thick tissue constructs. Vascular networks provide cells throughout the tissue with adequate oxygen and nutrients; cells located within thick un-vascularized tissue implants eventually die due to oxygen and nutrient deficiency. Vascularization has been identified as one of the key components in the field of tissue engineering. In order to fabricate biomimetic tissue which accurately recapitulates our native tissue environment, in vitro pre-vascularization strategies need to be developed. In this review, we describe various in vitro vascularization techniques developed recently which employ different technologies such as bioprinting, microfluidics, micropatterning, wire molding, and cell sheet engineering. We describe the fabrication process and unique characteristics of each technique, as well as provide our perspective on the future of the field.